Brhat kshetrasamāsa : Jaina d[r]shṭie mahābhūgola - Jinabhadragaṇi (Saṅghavī Ambālāla Ratnacanda Jaina Dhārmika Ṭrasṭa ; prāptisthāna Bī. E. Śāha, 1978)
Medieval Jain work on the geography of the world.